Students’ Perspective of Entrepreneur Character Education Value in Historical Figure Learning Materials - Toto Suharya; Nana Supriatna; Leli Yulifar; Encep Supriatna; Ema Agustina (Universitas Pendidikan Mandalika, 2023)
The study aims to describe students' perspectives on the values of character education as entrepreneurs from teaching materials for learning historical figures. The value of character education as an entrepreneur is a must for students as a form of relevance in facing the global era. This research used a qualitative approach with descriptive methods. Data were collected by observation, and questionnaires were distributed online to 50 students taking entrepreneurship courses at Padalarang 2 Public High School, West Bandung. Data were presented as average values and percentages, then narrated according to additional observational data. The data analysis process included data collection, reduction, presentation, and conclusion. The study's results found four values of character education as entrepreneurs from the four stories of historical figures (entrepreneurs), namely creative, courageous, survival and independent. This finding is relevant to the value of character education mandated in implementing the educational process in Indonesia. This study presents different findings due to the concept of the value of character education aimed at building graduates as entrepreneurs and being able to create jobs. It means that the values of character education that must be understood can be applied to various fields of human life by current global needs.